KOMUNIKASI EFEKTIF DALAM KEPEMIMPINAN PENDIDIKAN ISLAM - Amiruddin, T (Universitas Islam Negeri (UIN) Sumatera Utara, 2022)
This article aims to explain about effective communication in Islamic education leadership which includes; (1) Effective communication. (2) Islamic education leadership. (3) Effective communication relationships in Islamic education leadership. Effective communication in Islamic education leadership can be concluded several things as follows: (1) Effective communication is communication which in the process can produce changes in perception, behavior and understanding between the communicator and the communicant can be obtained. (2) Islamic education leadership is an effort to manage Islamic educational institutions carried out by a leader so that the process of teaching and learning activities in Islamic educational institutions is as expected and in accordance with the vision and mission of Islamic educational institutions. educational institutions. (3) An effective communication relationship in Islamic education leadership is needed with the aim of being able to achieve the goals of managing Islamic educational institutions by a leader, because to be able to achieve the goals of Islamic education effectively and efficiently, interaction with all elements of the educational institution environment must be built by the leader. accompanied by effective communication between a leader and all educational staff and employees.